Pemanfaatan Media Cyber Konseling Dalam Meningkatkan Mutu Layanan Bimbingan Konseling di Sekolah MAN 3 Langkat - Harahap, Ade Chita Putri; Hasibuan, Ahmad Anas; Lestari, Ayu Ari; Asmaida, Asmaida; Indriany, Dina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cyber counseling media can be an effective tool to improve the quality of guidance and counseling services in MAN 3 Langkat School. This media can help students who are difficult to reach directly to get counseling, provide easy access, improve the effectiveness and efficiency of services, expand the reach of services, and increase safety. However, in using cyber counseling media, attention must be paid to several things such as privacy and security of student data, technological security, and applicable regulations. The school needs to ensure that cyber counseling services are carried out in compliance with professional ethics and applicable laws in Indonesia. In this case, cyber counseling media can help improve the quality of guidance and counseling services in MAN 3 Langkat School Keywords: cyber counseling media, counseling services,.